Crime-related events identification based on text analytics approach - Mamyrbayev, Orken (Routledge, Taylor & Francis Group, 2025)
"As modern society is extremely dependent on the Internet, social net-works and developing technologies, a threat to the security of both the individual and society as a whole has emerged. The openness and global nature of the Internet create opportunities both for criminals, who can use the available information for criminal purposes, and for law enforcement officials. Police officers, in turn, can deal with the preventive processing of data from the Internet in order to prevent crimes. This type of data analysis can detect illegal or criminal actions even at the stage of their formation. Crime-Related Events Identification Based on Text Analytics Approach describes the possibilities of extracting crime-related facts from semi-structured information from various Internet sources, so that crime can be combatted. The book is aimed at police officers and IT-professionals working in online investigations"-- Provided by publisher